Mitochondrial dysfunction bridges negative affective disorders and cardiomyopathy in socially isolated rats: Pros and cons of fluoxetine. (2nd January 2017) - Sonei, Nazanin; Amiri, Shayan; Jafarian, Iman; Anoush, Mahdieh; Rahimi-Balaei, Maryam; Bergen, Hugo; Haj-Mirzaian, Arya; Hosseini, Mir-Jamal
Abstract: Objectives Depression is tightly associated with cardiovascular comorbidity and accounts for high financial and social burden worldwide. Mitochondrial dysfunction contributes to the pathophysiology of depression and cardiovascular disorders; its contribution to depression-cardiovascular comorbidity has not yet been investigated.Methods Adolescent rats were subjected to 4 weeks of isolation (social isolation stress or SIS) or social conditions (control), and then they were divided into treatment (fluoxetine, 7.5 mg/kg/day for 21 days) and non-treatment groups. After different housing conditions and treatment, animals were evaluated by behavioural tests ( n = 6–8) and mitochondrial assessments ( n = 3) of brain and cardiac tissues.Results We found that juvenile SIS induced behavioural abnormalities and mitochondrial dysfunction in adulthood. We showed that juvenile SIS was associated with impaired respiratory chain complex, which leads to reactive oxygen species formation, oxidative damage and ATP abatement in both brain and heart. Administration of FLX (7.5 mg/kg/day) during the isolation period attenuated the effects of SIS on the brain mitochondria and behavioural abnormalities, but had little or no effect on SIS-induced mitochondrial dysfunction in cardiac tissue.Conclusions This suggests that juvenile SIS predisposes the co-occurrence of depression and cardiovascular disease through mitochondrial dysfunction and that therapeutic effect of fluoxetine is partly mediated by its effect on mitochondrial function.